An Analysis of Expressive Functional Language in the Movie A Man Called Otto - Giska, Ni Putu Ayu Ngurah Giska Anjani; Ni Wayan Suastini (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
With an emphasis on how the characters' speech reflects their emotional states and the dynamics of their relationships, the current research attempts to analyze the usage of expressive language functions in the 2022 movie A Man Called Otto. Using information from the speech of the main character, Otto Anderson, as well as the speech of the supporting characters who affect Otto's emotional reactions, the current research uses a qualitative descriptive approach. Data were collected through repeated observation of the film, involving transcription and contextual note-taking that captured setting, interlocutors, and emotional tone. Content analysis was used to categorize the data according to Halliday’s (1973) theory of language functions, with particular emphasis on the expressive or personal function. The findings reveal that Otto’s dialogue predominantly features emotive, affective, and assertive expressions, while supporting characters provide empathetic and encouraging utterances that influence the emotional progression of the narrative. The study contributes to linguistic and cinematic discourse analysis by offering a detailed account of how expressive functions are structured both syntactically and contextually within film dialogue.